2015
DOI: 10.1521/jscp.2015.34.8.705
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concealment: Integrative Review and Working Model

Abstract: an extensive empirical literature has focused on the self-concealment (SC) construct. in this article, we review 137 studies that used the Self-Concealment Scale (SCS) with varied populations (e.g., adolescent; intercultural; international; lesbian, gay, and bisexual; and intimate partner). We propose a working model for the psychology of SC and the mechanisms of action for its effects on well-being. a dual-motive conflict between urges to conceal and reveal is seen to play a central role in these health effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
113
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 219 publications
(64 reference statements)
13
113
1
8
Order By: Relevance
“…A complex set of psychological processes and behavioral factors seems to contribute to the effect of self‐concealment on distress. Among others, it has been suggested that concealment behaviors may prevent the individual opportunity to reduce distress through disclosure or to gain social support . Indeed, social support and other factors, such as empathy and gender, were found to be related to concealment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complex set of psychological processes and behavioral factors seems to contribute to the effect of self‐concealment on distress. Among others, it has been suggested that concealment behaviors may prevent the individual opportunity to reduce distress through disclosure or to gain social support . Indeed, social support and other factors, such as empathy and gender, were found to be related to concealment.…”
Section: Introductionmentioning
confidence: 99%
“…disclosure or to gain social support. 14,15 Indeed, social support and other factors, such as empathy and gender, were found to be related to concealment. Accordingly, lower perception of empathy from the spouse, lower intimacy, and greater perception of avoidant behaviors and criticism from the spouse are associated with higher levels of holding back from talking about cancer-related concerns.…”
mentioning
confidence: 96%
“…Consistent with the hypothesis for the current study as well as with research findings from other CSI groups (Larson et al, 2015), concealment was significantly and positively correlated with and predictive of distress and adverse impact of stuttering on quality of life among AWS. A useful framework for understanding how concealment might negatively impact psychological health is to conceptualize concealment as a form of "safety behavior" that AWS use to minimize the probability of negative social outcomes related to stuttering.…”
Section: Concealmentsupporting
confidence: 91%
“…D. Jackson & Mohr, 2016;Riggle et al, 2017;Schrimshaw et al, 2013), multiple sclerosis (Cook et al, 2017), and histories of intimate partner violence (Sylaska & Edwards, 2014) and substance abuse (Luoma, Guinther, Potter, & Cheslock, 2017). Larson, Chastain, Hoyt, and Ayzenberg (2015) conducted a meta-analysis of 137 studies that used the Self-Concealment scale to measure concealment with various populations (e.g. adolescents, sexual minorities, intimate partner violence, etc.).…”
Section: Concealmentmentioning
confidence: 99%
“…Larson and Chastain (1990) state that self-disclosure is often a hallmark of a thriving therapeutic relationship (i.e., between therapist and patient) and that the concealment of traumatic events has negative health outcomes. Research has shown a strong negative correlation between self-concealment and help-seeking attitudes as well as between self-concealment and therapy outcomes (Larson, Chastain, Hoyt, & Ayzenberg, 2015). Therefore, self-concealment is generally associated with negative health outcomes both concurrently and subsequently.…”
Section: Measures Of Emotional Expressivitymentioning
confidence: 99%